8n+(-1)(1n+(-3))=

Simple and best practice solution for 8n+(-1)(1n+(-3))= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8n+(-1)(1n+(-3))= equation:


Simplifying
8n + (-1)(1n + (-3)) = 0
8n + -1(1n + -3) = 0

Reorder the terms:
8n + -1(-3 + 1n) = 0
8n + (-3 * -1 + 1n * -1) = 0
8n + (3 + -1n) = 0

Reorder the terms:
3 + 8n + -1n = 0

Combine like terms: 8n + -1n = 7n
3 + 7n = 0

Solving
3 + 7n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 7n = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 7n = 0 + -3
7n = 0 + -3

Combine like terms: 0 + -3 = -3
7n = -3

Divide each side by '7'.
n = -0.4285714286

Simplifying
n = -0.4285714286

See similar equations:

| 5(x-2)=17 | | 6+3x=4x+8 | | 2(-8-6k)=2k-2 | | 5=15a | | 2x+5y=1700 | | -7-3(4-4m)=-115 | | 1/2(2x-10) | | 2(x-5)+3x-=-15 | | 9(v+3)-3v=3(2v+3)-13 | | -2(2x-1)=2 | | 0.1(x+20)-0.03(x-40)=1.1 | | -6-2x=4(2x-4) | | 3q-7a+12=32 | | 0.65x(20)=0.25(40) | | (1/2)+2x=(3/5) | | 12x+4y-17x+2y+8z+15= | | -8x+-6=4 | | -18z=3(-z+6)+2 | | x+3/3-x/4=x-2/5 | | -0.3(y+6)=-2.4(y-1) | | x-(9+8)=-3 | | -4y-3(5y+2)=-1+4(-9-y) | | 2(5y-3)=34 | | 2+2/3= | | -3x^2-15x-12=0 | | x/4-x/8=80 | | 6=x+2.3 | | 8(x+4)=2(4x+2)+28 | | 12-62=-4-2z | | x/14+2x/4=24 | | 7x-14+1=-34 | | 1/3x=x-12 |

Equations solver categories